ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI DALAM MEMENUHI KEWAJIBAN MEMBAYAR PAJAK - Vivin S. Manafe; Nonce F. Tuati; Irwan Irwan (JAKA - Jurnal Jurusan Akuntasi, 2020)
This research aims to find out the factors that influence the level of compliance of individual taxpayers in fulfilling their tax obligations at KPP Pratama Kupang. The population in this study amounted to 134.047 who were registered individual taxpayers at KPP Pratama Kupang. The sampling technique is Accidental Sampling with a sample of 100 respondent individual taxpayers. The method used to collect data is the questionnaire method. Data analysis method used is descriptive analysis, classic assumption tests and multiple linear regression with the help of SPSS 21 program for windows.The results of research partially variable quality of taxation services have a positive and significant effect on compliance of individual taxpayers at KPP Pratama Kupang, it is proven by value tamount > ttable (2,190 > 1,98498) significance level of 0,031<0,05 and regression coefficient value of 0,185. Tax knowledge has a positive effect and significant effect on compliance of individual taxpayers at KPP Pratama Kupang, it is proven by value tamount > ttable (2,267 > 1,98498) significance level of 0,026<0,05 and regression coefficient value of 0,281. And Tax awareness has a positive effect and significant effect on compliance of individual taxpayers at KPP Pratama Kupang, it is proven by value tamount > ttable (3,781 > 1,98498) significance level of 0,000<0,05 and regression coefficient value of 0,416. Based on simultaneous tests of three independent variables that have a positive and significant effect on individual taxpayer compliance, this is evidenced by the value Famount > Ftable (19,213 > 2,70) at the level of significance of 0,000<0,05.